PENGARUH KOMPENSASI FINANSIAL, KOMPLEKSITAS TUGAS, DAN LOCUS OF CONTROL PADA KEPUASAN KERJA AUDITOR - Nirmala Hartha, Cok; Nyoman Badera, I Dewa (E-Jurnal Akuntansi, 2015)
Performance auditors play an important role in business development both in micro and macro. This is due to the auditor's opinion issued on the financial performance of a company will influence the decision-making parties either outside or inside the company. This study was to determine the effect of financial compensation, the job complexity, and locus of control on the job satisfaction of auditors with a sample of nine firm’s public accounting at Bali. This study using parametric inferential statistics and multiple linear regression analysis techniques. Transformation technique using the method of succesive intervals (MSI).Conclusions This study shows that financial compensation, the complexity of the task, and locus of control respectively - each significant positive effect on job satisfaction auditors. This means that the better financial compensation, the more clearly the increasing job complexity and the locus of control, the auditor's increasing job satisfaction
Keywords: financial compensation, the complexity of the task,locus of control, job satisfaction auditor